HIV Disclosure to the Child/Adolescent in Central and West Francophone Africa - (:unkn) unknown (My University, 2019)
We report the attitudes and practices of health care workers involved in the disclosure process to adolescents living with HIV (ALHIV) in a network including West and Central African French- speaking countries, and the experiences of young living with HIV (YLHIV). During a three-day workshop in Abidjan, Côte d’Ivoire, caregivers (doctors, psychologists, social workers) from 19 pediatric HIV treatment sites shared their practices and difficulties, and four YPLHIV their own disclosure experience. Thirty five participants from eight West/Central African countries (Benin, Burkina Faso, Ivory Coast, Cameroon, Mali, Democratic Republic of Congo, Senegal, Togo) contributed: 14 doctors, eight psychologists, six counselors, three social workers. The experience of the centers was variable, but the age at disclosure was late: 34% of 1296 adolescents between 10 and 12 years of age knew their status. The median age at disclosure was 13 years (range: 11-15 years). The practice of the disclosure was often complex, because of multiple factors (fear of the parents of the breaking of the secrecy, lack of communication between professionals). The individual disclosure was the main practice. Four centers practiced HIV disclosure in group sessions to facilitate mirror support, and one used peer-to-peer support. YPLHIV have advocated for an earlier disclosure, from 10 years. In West and Central Africa, the process of HIV disclosure remains complex for parents and caregivers, and occurs too late. The development of a good practice guideline for HIV disclosing adapted to socio-cultural contexts should help to improve this process.
Keywords: African Research